Hybrid laser ablation-single point diamond turning machining process for CVD-silicon carbide ceramics. (1st January 2013) - Ravindra, Deepak; Patten, John; Jacobsen, Ronald
Silicon carbide (SiC) is an advanced engineered ceramic material appropriate for operation in extreme environments. Manufacture of components from this material is extremely challenging due to its high hardness, brittle characteristics and poor machinability. Severe fracture can result when machining SiC due to its low fracture toughness. However, prior research has shown that ductile regime machining of silicon carbide is possible. This paper reports improvement of the surface quality of a chemically vapour deposited (CVD) polycrystalline SiC (3-C) material by using a hybrid laser ablation – single point diamond turning (SPDT) machining process. This work also emphasised increasing the material removal rate (MRR) and minimising the diamond tool wear. Besides the surface finish analysis, subsurface damage analysis was also done on the laser ablated and single point diamond turned surfaces to compare the nature of these processes in terms of subsurface damage.